Profitability Differences Between Steers and Heifers - Williams, Christopher L.; Langemeier, Micheal R.; Mintert, James; Schroeder, Ted C. (My University, 1993)
This publications examines the differences in sale price, feeder price, feed conversion, and average daily gain all to help explain variation in feeding profit differences between steers and heifers.
MF1075_1993_08
Keywords: MF1075; Livestock; Economics; MF